Perkawinan Cacat Mental dalam Perspektif Hukum dan HAM - Ahmad Khoirul Anwar Hidayat; Rohmah Maulidia (Institut Agama Islam Negeri Ponorogo, 2024)
Mentally handicapped marriages are a rare phenomenon because, generally, marriages are given to those who have above-average abilities. These mentally disabled sufferers have a level of intelligence. They are unable to adapt to environmental demands and fear that they will not be able to control their emotions or will not be able to mature in facing a problem. This qualitative research with a field approach aims to determine the legal status of marriage and provide the rights and obligations of husbands and wives with mental disabilities in Karangpatihan and Ngabar from a legal and human rights perspective. The research findings are: 1) The marriage is religiously valid when viewed from the purpose of the marriage. With the condition that it is valid if there is a guardian's permission, as in the opinion of Imam Syafi'i, Hanafi, and Hanbali, and the marriage is not valid according to the rules of taklīfi, because a person who experiences mental disorders does not have the appropriateness to be seen in his actions, 2) Fulfillment of the rights and obligations of people with disabilities mental issues such as the right to justice and legal protection, the right to education, the right to work, the right to health and the right to social welfare have not all been fulfilled.